Zamzam Water: Influence of Containers on Ionic Concentration and In-vitro Cytotoxic Effects on U87 Cell Line - Mohd Ekhwan, Toriman; Nasir, Mohamad; Ahmad Zubaidi, A.latif; Nor Hidayah, Abu Bakar (2016)
Zamzam is holy water believed by Muslim to have remedial power for all kinds of diseases. It contains many electrolytes and the concentration of the electrolytes may be affected by the types of container used for its storage. This study was carried out to determine the difference in ions concentration of Zamzam water stored in plastic and glass containers, and to determine cytotoxicity effects of Zamzam water against U-87 cell line (human primary glioblastoma cell line). Ion Chromatography (IC) was used to analyze the concentration. The analyzed anions in the Zamzam water include bromide, chloride, phosphate, nitrite, nitrate, sulfate and fluoride whereas the cations were ammonium, lithium, potassium, sodium, calcium and magnesium. Subsequently, MTT assay was used to determine the cytotoxicity of Zamzam water on U-87 cell line. This study reveals that Zamzam water anions and cations concentration was not statistically significant neither in plastic nor glass container. In addition, the Zamzam water did not cause any toxicity on the U87 cell line. We postulate that types of container do not have much influence on the ion concentration of Zamzam water and it is non-toxic on U87 cell line.